Functional components of walnuts: a review focusing on native and cultivated species - Fukasawa, Ritsuko; Miyazawa, Taiki; Abe, Chizumi; Bhaswant, Maharshi; Toda, Masako (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2024)
Walnuts are consumed worldwide as healthy food and are rich in functional components. There are several species of walnuts including Japanese native walnuts. It is well known that native walnuts contain more phytochemicals than cultivated ones. Therefore, the composition of the beneficial components found in native walnuts is of scientific interest. This review aimed to summarize the recent findings and potential uses of native walnuts, including their (1) use as food, (2) functional components (general composition, fatty acids, peptides, phytosterols, tocopherols, polyphenols, and other components), and (3) health-related prospects. Through this review, unexpectedly, we found that even though many are interested in the health benefits of Japanese native walnuts, which have functional components much differ to cultivated species, there is limited information on their contents. This review suggests a need to clarify the detailed amounts of these components.